Years of life that could be saved from prevention of hepatocellular carcinoma. Issue 7 (11th February 2016) - Cucchetti, A.; Trevisani, F.; Bucci, L.; Ravaioli, M.; Farinati, F.; Giannini, E. G.; Ciccarese, F.; Piscaglia, F.; Rapaccini, G. L.; Di Marco, M.; Caturelli, E.; Zoli, M.; et al.
Summary: Background: Hepatocellular carcinoma (HCC) causes premature death and loss of life expectancy worldwide. Its primary and secondary prevention can result in a significant number of years of life saved. Aim: To assess how many years of life are lost after HCC diagnosis. Methods: Data from 5346 patients with first HCC diagnosis were used to estimate lifespan and number of years of life lost after tumour onset, using a semi‐parametric extrapolation having as reference an age‐, sex‐ and year‐of‐onset‐matched population derived from national life tables. Results: Between 1986 and 2014, HCC lead to an average of 11.5 years‐of‐life lost for each patient. The youngest age‐quartile group (18–61 years) had the highest number of years‐of‐life lost, representing approximately 41% of the overall benefit obtainable from prevention. Advancements in HCC management have progressively reduced the number of years‐of‐life lost from 12.6 years in 1986–1999, to 10.7 in 2000–2006 and 7.4 years in 2007–2014. Currently, an HCC diagnosis when a single tumour <2 cm results in 3.7 years‐of‐life lost while the diagnosis when a single tumour ≥2 cm or 2/3 nodules still within the Milan criteria, results in 5.0 years‐of‐life lost, representing the loss of only approximately 5.5% and 7.2%, respectively, of the entire lifespan from birth. Conclusions: Hepatocellular carcinoma occurrence results in the loss of a considerable number of years‐of‐life, especially for younger patients. In recent years, the increased possibility of effectively treating this tumour has improved life expectancy, thus reducing years‐of‐life lost.